PTSD As Portrayed in Finn’s The Woman in The Window and Murakami’s Colorless Tsukuru Tazaki and His Years of Pilgrimage: A Comparative Literature - Fadillah, Adil (Jurnal Pendidikan Indonesia, 2021)
This thesis is entitled “Post-Traumatic Stress Disorder as Portrayed in A.J. Finn’s Novel The Woman in the Window and Haruki Murakami’s Novel Colorless Tsukuru Tazaki and His Years of Pilgrimage: A Comparative Literature Analysis”. The writer is interested in analyzing the two novels because they have the same motive is Post-Traumatic Stress Disorder. In this thesis the writer uses two novels as the object, there is The Woman in the Window (2018) from England and Colorless Tsukuru Tazaki and His Years of Pilgrimage (2013) from Japan. This study aims to find out how Post-Traumatic Stress Disorder is portrayed in the two literary works and to find the affinities and differences regarding the issue in forms of Post-Traumatic Stress Disorder that the main characters are suffering from using Post-Traumatic Stress Disorder‘s theory by American Psychiatric Association through the fifth edition of The Diagnostic and Statistical Manual of Mental Disorders (DSM-V). Both main characters of the two literary works, Anna Fox and Tsukuru Tazaki are suffering from Post-Traumatic Stress Disorder. The study also involves looking at the intrinsic elements to look at the affinities and differences found in the two literary works. In completing the analysis, the writer uses the descriptive qualitative method which represents all the data in the forms of words and sentences. The writer collects data from various sources including The Woman in the Window by A.J. Finn, Colorless Tsukuru Tazaki, and His Years of Pilgrimage by Haruki Murakami, relevant books, articles, and journals to support the analysis. Based on the results of the analysis it can be concluded that the two literary works show affinities and differences regarding Post-Traumatic Stress Disorder that is experienced by the two main characters of both literary works.